Returns to Education and Human Capital Depreciation in Spain - Ines P. Murillo (European Regional Science Association (ERSA), 2006)
The main objective of the present paper is to analise the differences in returns to education and rates of human capital depreciation between regions in Spain, during the period 1995-2002. To this end, the theoretical framework proposed by Raymond & Roig (2004) is used to incorporate the depreciation of human capital into the analysis of the private returns on education. Aditionally, the distinction between the two sources of human capital depreciation is approached by means of an estimation by sector –Neuman & Weiss (1995)- and an estimation by occupation.
Keywords: 330